INCLUSIVE EDUCATION: EDUCATION POLICY IN ENSURING THE RIGHT TO EDUCATION HUMAN - Rafii, Muhammad; Dahlistianto, Tomi; Munawaroh, Munawaroh; Novanda, Ramazani (Universitas Islam Negeri Sumatera Utara Medan, 2021)
The discussion of inclusive education has become a serious concern for researchers, education observers and education practitioners. However, several studies that have been conducted show that this is less positive for the practice of inclusive education in some educational institutions. This is because inclusive education policies have not been comprehensively understood by stakeholders and leaders of an educational institution. Therefore, the discussion of this article aims to construct education and inclusive education policies that are able to protect the right to education. This research was conducted through the use of library data sources and the use of policy documents such as draft policies and regulations related to inclusive education. The study in this article finds the fact that inclusive education policies do not yet have a strong commitment and fluency in discussing regulations and implementing inclusive education policies in every educational institution. Although on the one hand the right to education has actually been guaranteed by law and the mandate of the establishment of the Unitary State of the Republic of Indonesia. Inclusive education is education that is disability-friendly and anti-discrimination. Thus, this spirit becomes the basis and relevance for guaranteeing the right to education for every community. The conclusion of this article is that education is a right for every citizen that must be provided and guaranteed by the state. Therefore, inclusive education policies that are binding must be published and controlled by government authorities in their implementation in every educational institution